Prototipe smart home berbasis mikrokontroler arduino dan smart phone - Mafruddin Mafruddin; Sulis Dri Handono; Avin Darma Irawan (TURBO [Tulisan Riset Berbasis Online], 2020)
In this study, a home electrical control system and electronic components were  designed using an Arduino Uno R3 microcontroller equipped with a motion sensor and connected to a Bluetooth module and a GSM (Global System for Mobile Communications) SIM (Subscriber Identification Module) module. In addition, the Smart Home prototype will also be equipped with earthquake detection sensors, fire sensors and sensors as soon as possible to deal with early earthquakes and fire detection. The purpose of research is to see the performance of the smart home system. The research method used is a research method with methods and making and testing Smart home prototypes. Testing is done by running the system to see the performance of the system being made. From the research results it can be ignored that the electrical control system and electronic components made using the Arduino Uno R3 microcontroller and the Bluetooth module and the GSM SIM module can work properly, the electrical system and electronic components can be turned on and off using a GSM SIM and Bluetooth module. The security system uses motion sensors and a GSM SIM module to work properly, the system can send SMS (Short Message Service) notifications to homeowners if human movement. The earthquake and fire detection sensor system in the smart home prototype can work properly, the system can turn on notification alarms when an earthquake and wait for fire and as soon as possible.Keywords: Mikrokontroler arduino, Smart phone, Smart home.